The The Impact of Foreign Direct Investment on Manufacturing Company Innovation Opportunities in ASEAN: A CDM Model Analysis - Yuliana, Tarisha; Rohman, Ibrahim Kholilul (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2024)
ASEAN is known as a region that has several comparative advantages that can attract and encourage increased FDI. Indonesia as the 2023 ASEAN Chairmanship, raised the theme "ASEAN Matters: Epicentrum of Growth". However, there are two fundamental problems, such as FDI restrictions in the telecommunications sector and low R&D activity which has implications for low innovative activity leading to deindustrialization in ASEAN. Thus, to answer this problem, this study will analyse the effect of FDI on innovation opportunities for manufacturing companies using the CDM model approach. Through the Heckman Selection Model and Probit methods, it was found that the presence of FDI tends to reduce R&D spending. In fact, the results of R&D spending have a positive and significant relationship to manufacturing company innovation opportunities. In addition, it was found that innovation in ASEAN was not from R&D activities, but came from foreign R&D that had been carried out in their home countries.